2001
DOI: 10.1038/sj.cdd.4400881
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IL-1β generation by Pseudo-ICE and ICEBERG, two dominant negative caspase recruitment domain proteins

Abstract: We report here the identification and functional characterization of two new human caspase recruitment domain (CARD) molecules, termed Pseudo-interleukin-1b converting enzyme (ICE) and ICEBERG. Both proteins share a high degree of homology, reaching 92% and 53% identity, respectively, to the prodomain of caspase-1/ICE. Interestingly, both Pseudo-ICE and ICEBERG are mapped to chromosome 11q22 that bears caspases-1, -4-and -5 genes, all involved in cytokine production rather than in apoptosis. We demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
195
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(201 citation statements)
references
References 45 publications
(48 reference statements)
4
195
2
Order By: Relevance
“…ICEBERG proteins are intracellular regulators of caspase-1 activation and could play a role in the regulation of IL-1b secretion and NF-kB activation during the proinflammatory cytokine response (Humke et al, 2000;Druilhe et al, 2001), NFkB is a well-defined radiation-responsive transcription factor (Thanos and Maniatis, 1995). Furthermore, NF-kB is associated with the cell cycle, and we found that cyclin A2 (CCNA2) was downregulated.…”
Section: Genes Related To Apoptosis and Cell Cyclementioning
confidence: 64%
“…ICEBERG proteins are intracellular regulators of caspase-1 activation and could play a role in the regulation of IL-1b secretion and NF-kB activation during the proinflammatory cytokine response (Humke et al, 2000;Druilhe et al, 2001), NFkB is a well-defined radiation-responsive transcription factor (Thanos and Maniatis, 1995). Furthermore, NF-kB is associated with the cell cycle, and we found that cyclin A2 (CCNA2) was downregulated.…”
Section: Genes Related To Apoptosis and Cell Cyclementioning
confidence: 64%
“…27 Therefore, this type of human caspase-12 may be comparable with two other human CARD-only proteins, ICEBERG and COP/Pseudo-ICE, residing on the same chromosome (Figure 1b). [29][30][31] Similar to the human pseudocaspase-12 gene, ICEBERG and COP/Pseudo-ICE are encoded by caspase-like genes that have acquired premature nonsense mutations leading to the production of truncated molecules. Both ICEBERG and COP/Pseudo-ICE closely resemble the prodomain of caspase-1.…”
Section: Human Caspase-12 Gene Encodes An Aberrant Caspasementioning
confidence: 99%
“…Furthermore, both proteins interact with the CARD present in the prodomain of caspase-1, preventing the activation of this caspase and the subsequent generation of IL-1b. [29][30][31] Interestingly, COP/ Pseudo-ICE is also capable of activating NF-kB and binding to the CARD of RIP2, a known inducer of NF-kB activation. 29,31 ICEBERG does not bind to RIP2 nor does it signal to NF-kB activation.…”
Section: Human Caspase-12 Gene Encodes An Aberrant Caspasementioning
confidence: 99%
See 2 more Smart Citations